Ink-jet printing for Plasma-treated Cotton Fabric with Biomaterial - C.W. Kan; C.W.M. yuen; W.Y. Tsoi; C.K. Chan (ASEAN Journal of Chemical Engineering, 2011)
Currently, sodium alginate is commonly used for preparing the printing medium for digital ink-jet printing due to its ready solubility and excellent stability even at high-temperature fixation treatments. Similar to sodium alginate, chitosan is also widely used as novel biomaterial. As a natural polymer, sodium alginate and chitosan are biocompatible, biodegradable and non-toxic. Therefore, chitosan may be used as a chemical for preparing printing medium for digital ink-jet printing for cotton fabric. Recently, low temperature plasma (LTP) treatment has proved to be an effective pretreatment method for the improving coating process by altering the surface properties of the material without much changing of the bulk properties. Thus, the aim of this study was to investigate the possibility of applying LTP treatment as pretreatment process to enhance the coating of printing medium, i.e. sodium alginate and sodium alginate/chitosan mixture, so as to improve the final properties of the digital ink-jet printed cotton fabric.